A comparative pharmacokinetic and tolerability analysis of the novel orotic acid salt form of tenofovir disoproxil and the fumaric acid salt form in healthy subjects - Kim YK; Choi MJ; Oh TY; Yu KS; Lee S (Dove Medical Press, 2017)
Yu Kyong Kim,1 Mun Ju Choi,2 Tae Young Oh,2 Kyung-Sang Yu,1 SeungHwan Lee1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 2Dong-A ST Co., Ltd., Seoul, Republic of Korea Abstract: A novel orotic acid salt form of tenofovir disoproxil (DA-2802) was developed and is expected to replace the fumaric acid salt form. The pharmacokinetic (PK) characteristics and tolerability profiles of DA-2802 were compared to those of tenofovir disoproxil fumarate (TDF, Viread®) in healthy subjects. A randomized, open-label, single-dose study was conducted in 36 healthy subjects using a two-treatment, two-period, and two-sequence crossover design. Subjects received a single oral dose of 319 mg DA-2802 or 300 mg TDF, during each period, with a 7-day washout. Serial blood samples were collected pre-dosing and up to 72 hours post-dosing in each period, for determination of serum tenofovir concentration, which was measured by ultra-performance liquid chromatography-tandem mass spectrometry. A non-compartmental method was used to obtain PK parameters of tenofovir. For comparison between the two tenofovir disoproxil salts, the 90% confidence intervals (90% CIs) of geometric mean ratios of DA-2802 to TDF for the maximum concentration (Cmax) and the area under the concentration–time curve to the last quantifiable concentration (AUC0–t) were determined. The tolerability profiles of tenofovir were assessed by evaluation of adverse events and vital signs, physical examination, ECG, and clinical laboratory tests. The serum tenofovir concentration–time profiles of DA-2802 or TDF were comparable in 32 subjects who completed the study. In both profiles, a two-compartmental elimination with first-order elimination kinetics in the terminal phase was reported in a few subjects, showing a secondary peak in the initial phase of elimination. The geometric mean ratio (90% CI) of DA-2802 to TDF was 0.898 (0.815–0.990) for Cmax and 0.904 (0.836–0.978) for AUC0–t. There were no clinically significant findings in the tolerability assessments. DA-2802 showed comparable PK characteristics and tolerability profiles to TDF. Keywords: phase I clinical trial, chronic hepatitis B virus infection, drug development